Sosialisasi Pandemik Covid-19 dan Diseminasi Konsep Kota Cerdas, Sehat, dan Tangguh Pandemik - yashinta kumala dewi sutopo; Muh. Yamin Jinca; Ananto Yudono; Mimi Arifin; Abdul Rahman Rasyid; Arifuddin Akil; Mukti Ali; Ihsan Latief; Laode M. Asfan; Azizah Putri Abdi (Faculty of Engineering UNHAS, 2020)
Covid-19, a global pandemic, demands active roles from everyone, including from educational institution. Department of Urban dan Regional Planning of University of Hasanuddin supports the Government and the society by organizing two community service activities as part of three pillars of higher education. The first activity is to advocate and raise public awareness on Covid-19 through educative, persuasive and animative approaches in the form of writings, photos, posters and videos posted via youtube and Instagram on April and May 2020 targeting minimal 1,000 viewers. The second activity is to disseminate concept of smart, healthy and resilient city as a planning effort anticipating for future pandemics through scientific, systemic, and collaborative approaches in the form of a virtual national seminar held on 24 September 2020 targeting minimal 300 participants. This paper aimed to describe the objectives, processes and results of these two activities as well as to enlighten the main ideas of the concept presented in second activity. Up to 10 October 2020, it was noted that a total of 4,037 reviewers have visited the social medias used in the first activity. A total of 1,008 requests entered the registration email of the organizer during 7 days prior to the second activity. A total of 584 participants from various universities, government agencies and planning/architectural consultants attended the second activity. The numbers of viewers and participations in both activities that exceeded the initial targets shows an optimum active role of the department in supporting the Government and the society based on to its field and capacity.